Recurrent idiopathic chylothorax - Heda Melinda D Nataprawira; Oma Rosmayudi; Syaiful Effendy (Indonesian Pediatric Society, 2004)
The chylous drainage may lead to highmorbidity and may even compromise survival becauseof the large amount of loss, that is, deficits inlymphocytes, protein, and immunoglobulin. Thetreatment of chylothorax is still debatable withdifferent therapeutic approaches i.e., purelyconservative with elemental diet or total parenteralnutrition, or surgical (early or late) with ligation ofthe thoracic duct, pleurodesis, or placement ofpleuroperitoneal shunts. The purpose of this reportis to describe a case of chylothorax in a 2-year-oldgirl which was recurrent and difficult to manage.